Two cases of small bowel necrosis due to intussusception secondary to abnormal proliferation of intestinal Peyer's patches in infants after MMR vaccination - Junzhao Zhu; Weiping Cheng; Youbo Xu; Yingqiang Guo; Lexiang Shi (BMC, 2024)
Abstract Background Intussusception is one of the most common acute abdominal conditions in pediatric patients, and if left untreated, it may result in intestinal necrosis and even death. The etiology of the disease is unknown and may be related to a variety of factors, and there are only limited reports of small bowel necrosis secondary to abnormal Peyer's node hyperplasia after MMR vaccination. Case presentation In this report, we present two infants who had an abnormal proliferation of Peyer's nodes secondary to intussusception eventually leading to small bowel necrosis after MMR vaccination. Conclusions Intestinal necrosis and infectious shock are the most common causes of infant mortality, and early detection and management are critical.